Examining the impact of Buerger-Allen exercises on alleviating muscle cramps in extubated patients - Sahoo Rashmita; Swain Mamata; Tripathy Pravati (Journal of Integrative Nursing)
Objective: This study aimed to evaluate the effectiveness of Buerger-Allen exercise (BAE) in reducing muscle cramps among recently extubated patients in the intensive care unit (ICU). Materials and Methods: A quantitative, quasi-experimental design was employed, involving 92 recently extubated ICU patients randomly assigned to either an experimental or control group. The experimental group underwent BAE, a three-step intervention targeting lower extremity circulation and muscle cramp reduction. The exercises included the elevation of lower extremities, foot and leg exercises, and a rest and recovery phase, administered twice daily for 10 days. The control group received standard nursing care without any specific exercise regimen. Muscle cramp severity was assessed using the modified Penn Spasm Frequency Scale before and after the intervention. Results: The experimental group showed a significant reduction in muscle cramp severity score postintervention, with the mean scores decreasing from 6.83 ± 1.66 to 4.22 ± 1.45 (t = 10.21, P = 0.001). The control group experienced a smaller reduction, with scores decreasing from 6.98 ± 1.57 to 6.43 ± 1.37 (t = 2.810, P = 0.007). Between-group analysis confirmed a significant difference postintervention, with the experimental group improving more (t = 8.242, P = 0.001). The Mann–Whitney U test also highlighted a significant difference between groups after the intervention (U = 494.5, P = 0.001), validating the effectiveness of BAE. Conclusion: BAE significantly reduces muscle cramp severity in recently extubated ICU patients, suggesting that this nonpharmacological intervention can effectively improve patient outcomes and aid in postextubation recovery.